العمل الخيري وأثره في التكافل الاجتماعي في ضوء مقاصد الشريعة " جمعية كافل اليتيم الجزائرية " أنموذجا - عمري، ساليم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This is a study that combines the rooting, branching, and application of the topic of charitable work, social solidarity and legal objectives, and the objectives of the research are summarized in introducing each of charitable work, its types, sources of funding and its banks, and the legal objectives, their ranks and relationship with it, social solidarity, its types, means, social effects, aspects of its realization, and the impact of work The charity in consolidating its foundations, supplementing by mentioning its intentional dimensions and its relationship to legitimate intentions and what are the limits of its ability to memorize the five essentials with needful and improvement purposes, then focus on the correct practical application of charitable work and mention areas of this with its realistic evidence and field applications, according to the study of its evaluation, trying to highlight the positive role Charitable work and focus on it and complete the deficiencies from the point of view of the objectives of Islamic law, and talk about the challenges and obstacles it faces in achieving its goals, the solutions and mechanisms proposed to get rid of these obstacles and how to properly and properly apply them, and in conclusion, a presentation of the experience of the Algerian National Orphan Society in its charitable work and its goals in serving orphans And widows, and their means and areas, and their impact on achieving compatibility This study is organized in the holding of qualitative studies, which depend on several scientific approaches, the inductive, deductive, and analytical approach, as well as the field approach, represented by personal interviews, and the researcher in this study concluded a set of results, the most important of which is the extent of effectiveness Charitable work in achieving social solidarity and legitimate purposes, and the need to pay attention to it, redress all its deficiencies and overcome all obstacles that hinder it, in order to achieve the desired goals in meeting the basic needs of society in accordance with the desired interest, and the researcher concluded his study with a set of recommendations.